Natural variation in stomatal dynamics drives divergence in heat stress tolerance and contributes to seasonal intrinsic water-use efficiency in Vitis vinifera (subsp. sativa and sylvestris). (20th December 2021) - Faralli, Michele; Bontempo, Luana; Bianchedi, Pier Luigi; Moser, Claudio; Bertamini, Massimo; Lawson, Tracy; Camin, Federica; Stefanini, Marco; Varotto, Claudio
Abstract : Stomatal behavior can play a critical role in leaf thermoregulation and water conservation in grapevine when light and vapor pressure deficit are changing rapidly. Abstract: Stomata control CO2 uptake for photosynthesis and water loss through transpiration, thus playing a key role in leaf thermoregulation, water-use efficiency (i WUE), and plant productivity. In this work, we investigated the relationship between several leaf traits and hypothesized that stomatal behavior to fast (i.e. minutes) environmental changes co-determines, along with steady-state traits, the physiological response of grapevine to the surrounding fluctuating environment over the growing season. No relationship between i WUE, heat stress tolerance, and stomatal traits was observed in field-grown grapevine, suggesting that other physiological mechanisms are involved in determining leaf evaporative cooling capacity and the seasonal ratio of CO2 uptake ( A ) to stomatal conductance ( g s ). Indeed, cultivars that in the field had an unexpected combination of high i WUE but low sensitivity to thermal stress displayed a quick stomatal closure to light, but a sluggish closure to increased vapor pressure deficit (VPD) levels. This strategy, aiming both at conserving water under a high to low light transition and in prioritizing evaporative cooling under a low to high VPD transition, was mainly observed in the cultivars Regina and Syrah. Moreover, cultivars with different known responses to soil moisture deficit or high air VPD (isohydric versus anisohydric) had opposite behavior under fluctuating environments, with the isohydric cultivar showing slow stomatal closure to reduced light intensity but quick temporal responses to VPD manipulation. We propose that stomatal behavior to fast environmental fluctuations can play a critical role in leaf thermoregulation and water conservation under natural field conditions in grapevine.